The Present Study Investigates the Efficacy of Direct Instruction in Enhancing Student Learning Outcomes Concerning the Solar System - Siswanto, Berlin; Andrijati, Noening; Avrilianda, Decky; Ellianawati, Ellianawati (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2025)
The objective of this study is to assess the efficacy of the Direct Instruction model in enhancing student achievement on the subject of the Solar System in the sixth grade at SDN Sumurlaban II. The present study employed a quasi-experimental design (pre-test–post-test control group) and comprised 40 students who were selected by random sampling. These students constituted the entire population of students in the sixth grade at the aforementioned school. Subsequently, the students were divided into two groups: 20 students in the experimental group (who received instruction using the Direct Instruction model) and 20 students in the control group (who received Konvensional instruction). The instruments employed in this study included a multiple-choice test and a short-answer test, as well as a classroom observation checklist. The collected data was subjected to statistical analysis, specifically the parametric t-test, to identify any significant differences in the pretest and posttest values. The findings of the present study demonstrate that the implementation of Direct Instruction has yielded a substantial enhancement in the academic performance of the students, particularly in the domain of abstract concepts such as the identification of the components of the Solar System, as well as the comprehension of concepts related to orbit, rotation, and revolution. This finding suggests that the Direct Instruction model is a viable teaching method in primary education, particularly in the context of systematically and structurally imparting scientific concepts.